The Drying Kinetics of Pre-Treated Sweet Potato Strips - Pestaño , Lola Domnina; Obregon , Fauve Ira Alexa V.; Silvano , Maria Blesy C.; Vicencio , Jeelaine G. (Contemporary Perspective on Science, Technology and Research Vol. 6, 2024)
Sweet potatoes are prone to the fungi, Rhizopus oryzae that results in fast spoilage upon delivery due to its moisture content (MC). This problem can be addressed by a drying process where a hot tray air dryer was used. The decrease in MC can prolong the shelf-life of the sweet potato. Also, pre-treating sweet potato with sodium metabisulfite results in unique flavor, color and texture attributes which are the main drivers of consumer acceptability of the products. Sweet potatoes were cut uniformly into 30x5x5 mm dimension. The sweet potato strips were soaked in 2%(w/v) Potassium Metabisulfite (KMS) solution at \(50^{°}\)C for 15 minutes and were drained under standard condition. The treated sweet potato strips were dried at 40°C, 50°C, \(60^{°}\)C until the constant weight was obtained. Laplace Transform Model, Non-Linear Decomposition Model, and Page Model are the three mathematical models that were compared to determine what is the best fit for the drying of the sweet potato. Based on data gathered, The Page model was found to be the most suitable to describe the drying characteristics of treated sweet potato strips with the least total error and highest coefficient of determination. The optimum drying temperature was 60°C with a drying time of 46 minutes to achieve 10% MC that inhibit the growth of Rhizopus oryzae. The pre-treatment of sweet potato strips avoids the undesirable changes such as the natural color and texture of sweet potatoes after air-drying.